Drop Impact Dynamics: Impact Force and Stress Distributions - Gordillo-Zavaleta, L (Annual Reviews Inc., 2021)
AbstractDynamic variables of drop impact such as force, drag, pressure, and stress distributions are key to understanding a wide range of natural and industrial processes. While the study of drop impact kinematics has been in constant progress for decades thanks to high-speed photography and computational fluid dynamics, research on drop impact dynamics has only peaked in the last 10 years. Here, we review how recent coordinated efforts of experiments, simulations, and theories have led to new insights on drop impact dynamics. Particularly, we consider the temporal evolution of the impact force in the early- and late-impact regimes, as well as spatiotemporal features of the pressure and shear-stress distributions on solid surfaces. We also discuss other factors, including the presence of water layers, air cushioning, and nonspherical drop geometry, and briefly review granular impact cratering by liquid drops as an example demonstrating the distinct consequences of the stress distributions of drop impact. © 2021 Annual Reviews Inc.. All rights reserved.